Immunization against Lamb Haemonchosis with a Recombinant Somatic Antigen of Haemonchus contortus (rHcp26/23) - García-Coiradas, Leticia (SAGE-Hindawi Access to Research, 2010)
Haemonchosis, caused by the abomasal nematode Haemonchus contortus, is a common parasitic disease of sheep. Our previous results showed that a soluble fraction from adult stages of the nematode (p26/23) induced partial protection against challenge. Recombinant DNA technology was applied to obtain a synthetic protein (rHcp26/23). Immunological assays (ELISA, Western blotting, and immunolocalization), using sera from lambs immunized with p26/23, confirmed the identity of the recombinant protein and demonstrated that the synthetic protein is equivalent to the purified protein employed in the previous immunoprophylaxis studies. Vaccination of lambs with 300 μg of rHcp26/23 and Freund's adjuvant elicited a notable specific antibody response. Immunization did not induce any significant protection after challenge with 16000 infective larvae of H. contortus, and comparable values for parasite faecal egg output, packed cell volume, and abomasal parasite burdens were found in vaccinated and control animals.